2020
DOI: 10.1186/s12870-020-02391-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Eutrema salsugineum EsMYB90 gene important for anthocyanin biosynthesis

Abstract: Background: Anthocyanins contribute to coloration and antioxidation effects in different plant tissues. MYB transcription factors have been demonstrated to be a key regulator for anthocyanin synthesis in many plants. However, little information was available about the MYB genes in the halophyte species Eutrema salsugineum. Result: Here we report the identification of an important anthocyanin biosynthesis regulator EsMYB90 from Eutrema salsugineum, which is a halophyte tolerant to multiple abiotic stresses. Our… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…The phenylpropanoid/flavonoid biosynthesis pathway is an important metabolic pathway in plants. For example, plant defense responses are associated with activation of the general phenylpropanoid pathway and anthocyanins are the end product of a branch of the phenylpropanoid/flavonoid biosynthesis pathway [ 74 , 75 ]. It has been shown that BBX proteins not only play an essential role in regulating photomorphogenesis [ 76 ], but also light-induced anthocyanin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The phenylpropanoid/flavonoid biosynthesis pathway is an important metabolic pathway in plants. For example, plant defense responses are associated with activation of the general phenylpropanoid pathway and anthocyanins are the end product of a branch of the phenylpropanoid/flavonoid biosynthesis pathway [ 74 , 75 ]. It has been shown that BBX proteins not only play an essential role in regulating photomorphogenesis [ 76 ], but also light-induced anthocyanin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The increased anthocyanin content in leaves, stems, flowers and fruit pods of EsMYB90 transgenic tobacco plants was caused by significantly up-regulated expression of anthocyanin biosynthesis genes in the previous study [37]. In order to clarify in depth Except for the above flavonoid metabolites, the contents of caffeic acid in hydroxycinnamoyl derivatives, 3-O-p-coumaroyl shikimic acid O-hexoside as well as chlorogenic acid methyl ester in quinate derivatives, esculetin (6,7-dihydroxycoumarin) and esculetin O-quinacyl esculetin O-quinic acid in coumarin also strongly increased (Figure 2A and Supplementary Table S3).…”
Section: Integrated Analysis Of Metabolite Profiling and Rna-seq In Phenylpropanoid/flavonoid Biosynthesis Pathwaysmentioning
confidence: 63%
“…The increased anthocyanin content in leaves, stems, flowers and fruit pods of Es-MYB90 transgenic tobacco plants was caused by significantly up-regulated expression of anthocyanin biosynthesis genes in the previous study [37]. In order to clarify in depth the specific roles of EsMYB90 in flavonoid pathways and unravel the regulatory mechanisms in place, we have performed the combined analysis of significantly differential metabolites and markedly differential expression genes (DEGs).…”
Section: Integrated Analysis Of Metabolite Profiling and Rna-seq In Phenylpropanoid/flavonoid Biosynthesis Pathwaysmentioning
confidence: 92%
See 2 more Smart Citations